An appraisal on the benefits and risks of agricultural biotechnology in developing societies - Okonkwo Onyebuchi Kingsley (Global Journal of Plant and Soil Sciences, 2017)
The most critical areas in the world for bringing economic prosperity and stability are the developing countries. Agricultural productivity in these countries must advance more rapidly to meet growing food demands and raise incomes while protecting the environment for future generations. Agricultural biotechnology has the potential to play a large role toward this achievement. Sadly, this opportunity remains a mirage for most developing societies because of numerous challenges that prevent them from benefiting from the technology. This review identified these challenges to include lack of effective leadership, poor funding of agricultural biotechnology research and development, lack of research focus and infrastructure, and inadequate human resources and expertise. It further appraised the benefits and risks of agricultural biotechnology to developing societies. Among the potential benefits of the technology are: an increase in the productivity of tropical commodities to meet future food needs, new opportunities for the use of marginal lands, and a reduction in the use of agrochemicals. However, associated with the technology are diverse questions of safety, ethics, and welfare. The review concluded with recommendations on the appropriate use and application of agricultural biotechnology in developing societies. They include adequate regulatory measures, public debate, human resource development and training, public-private sector collaboration, intellectual property management, and support from international development organizations.